2018
DOI: 10.1002/ijc.31782
|View full text |Cite
|
Sign up to set email alerts
|

Survival after the diagnosis of de novo malignancy in liver transplant recipients

Abstract: In the setting of liver transplant (LT), the survival after the diagnosis of de novo malignancies (DNMs) has been poorly investigated. In this study, we assessed the impact of DNMs on survival of LT recipients as compared to corresponding LT recipients without DNM. A nested case-control study was conducted in a cohort of 2,818 LT recipients enrolled in nine Italian centres between 1985 and 2014. Cases were 244 LT recipients who developed DNMs after LT. For each case, two controls matched for gender, age, and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…It is estimated that 50% of malignancies in transplant patients are in the head and neck region; however, the majority are cutaneous cancer, and only 4% to 6% are noncutaneous cancers . In a study from Italy that involved 2,818 liver transplant recipients, 244 identified subjects developed de novo malignancy, 15.5% of which were head and neck and thyroid gland cancers . Patients who developed head and neck cancer had a significantly lower survival .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that 50% of malignancies in transplant patients are in the head and neck region; however, the majority are cutaneous cancer, and only 4% to 6% are noncutaneous cancers . In a study from Italy that involved 2,818 liver transplant recipients, 244 identified subjects developed de novo malignancy, 15.5% of which were head and neck and thyroid gland cancers . Patients who developed head and neck cancer had a significantly lower survival .…”
Section: Discussionmentioning
confidence: 99%
“…3,5 In a study from Italy that involved 2,818 liver transplant recipients, 244 identified subjects developed de novo malignancy, 15.5% of which were head and neck and thyroid gland cancers. 15 Patients who developed head and neck cancer had a significantly lower survival. 15 Likewise, in a meta-analysis by Liu et al identified a 3.8-fold higher risk of head and neck cancer in liver transplant recipients compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of tumor recurrence was indeed much lower in the treated malignancy group than in the incidental malignancy group in the present study because patients in the treated malignancy group were naturally selected through long‐term observation after curative treatment. The risk of post‐transplant tumor recurrence in the treated malignancy group appears to be comparable to that of patients with post‐transplant de novo malignancy …”
Section: Discussionmentioning
confidence: 91%
“…A recent study demonstrated that the all-cancer 10-year survival in a large cohort of Italian liver transplant patients experiencing a malignancy was significantly lower as compared to that of liver transplant recipients without cancer (43 vs. 70%, HR = 4.66). The difference in survival was observed for both early and late mortality, although the effect was more pronounced in the first year after cancer diagnosis (188). These findings clearly point to the need to perform close oncologic monitoring during the post-transplant follow-up in order to ensure early cancer diagnosis and to improve survival.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%